The star fisher - Yep, Laurence, 1948- (New York, N.Y., U.S.A. : Puffin Books, 1992)
Fifteen-year-old Joan Lee and her family find the adjustment hard when they move from Ohio to West Virginia in the 1920s.
G6
Keywords: Chinese Americans -- Fiction; Moving, Household -- Fiction; Prejudices -- Fiction